Surveying Graduate and Professional Students' Perspectives on Library Services, Facilities and Collections at the University of Illinois at Urbana-Champaign: Does Subject Discipline Continue to Influence Library Use? - Tina E. Chrzastowski; Lura Joseph (Issues in Science and Technology Librarianship, 2006)
The University Library at the University of Illinois at Urbana-Champaign (UIUC) Services Advisory Committee has established a program to create a regular rotation of patron surveys. The program is an effort to answer basic questions about attitudes towards the library's services, facilities and collections. Modeled directly after those surveys designed and carried out at the University of Washington Libraries, the UIUC plan calls for an annual rotation of three surveys, each focused on a different user group. The first group surveyed (spring 2004) consisted of graduate and professional students, to be followed by undergraduate students (spring 2005) and faculty (spring 2006). Surveys will be conducted annually thereafter so that each user group will be surveyed every three years. Results from the first UIUC web survey, with 1400 respondents, revealed that graduate and professional students are very satisfied with their library experiences and the pattern of responses by subject discipline corresponds with the findings of Hiller (2002) at the University of Washington, but with some predicted shifts. "How-tos" for the web survey are discussed and included, along with a link to two sets of data analyses. In addition, lessons learned from the survey experience are discussed and suggestions are made for the presentation of data to successfully communicate survey results to decision makers. [ABSTRACT FROM AUTHOR]